Gender balance in Research Group Leadership at UiT: The Research group’s Basic Structure and Leadership roles - Duarte, Melina; Kochanska, Adrianna; Rönnblom, Malin (Septentrio Reports, 2021)
UiT The Arctic University of Norway has a decade-long tradition of channelling research through formally accredited research groups. These research groups have dynamic structures and networks, unlimited duration, a defined leader, and gather academics of all levels to pursue research on a common topic of interest. The formalisation of research groups at the institution followed strategies aimed at supporting the creation of more robust and resilient research communities and boost cutting-edge research produced at the university. Ten years after initiating the formalisation process, UiT has around 196 research groups distributed fairly evenly across faculties by their size. HELSE and HSL are the largest faculties and also the ones with the largest number of research groups. As of June 2020, 57% of these research groups were led by men. This shows that gender balance has been achieved in research group leadership at the university level in terms of numerical parity. While the formalisation of the research groups may have contributed to achieving this balance, data collected for this study represents an inaugural attempt to map gender-disaggregated research group leadership at UiT. This report shows that the gender distribution in research group leadership across faculties and departments or centres follows the remaining disparities existing in top academic positions (professor and docent) as they were observed in former studies conducted by the Prestige Project. This result is consistent since 93% of all research groups at UiT are led either by associate professors or professors. BFE, HELSE, and HSL are the most gender-balanced faculties, while IVT and NT are the least balanced. At IVT and NT faculties, 80% of the research groups are led by men. At the faculties that follow a level system for research groups (HSL and JUR), women currently lead more top-level groups than men. Despite the achievement of gender balance in research group leadership functions at UiT, a survey conducted by the Prestige Project that complements the dataset showed that gender shapes relevant differences regarding the basic structure of research groups and their leadership roles. Highlights of these differences can be systematised as follows: (1) The average size of research groups at UiT is 12.6 members. Men tend to lead smaller groups with a higher proportion of members holding 50% or more research contracts. (2) Most of the research groups at UiT follows a “stjerneklubb” structure, in which leaders are one of the several key researchers within the group. Three times more men than women reported leading a group with a “rakett” structure, in which the leader is the group’s key researcher. (3) Concerning the reported activity level following each groups evaluated potential from the leader’s perspective, men reported a higher maximal achievement of the group’s potential. At the same time, women indicated greater room for improvement. (4) Finally, regarding leadership and leadership roles, men have been more often appointed as leaders by the head of departments or centres, while women have more often been chosen by the group members. Furthermore, while both men and women in leadership roles engage equally in managerial tasks in their functions as research group leaders, men reported performing more of the tasks associated with a leadership role. Twice as many men reported that they set the group's research agenda and control the workflow of delegated tasks. We do not claim that these differences are necessarily negative since they can also be seen as a sign that gender balance increases the diversity of approaches in leadership at the university, which is a desirable aim in fostering excellence. The meaning of these differences has to be investigated further in future research.